A GM1 gangliosidosis mutant mouse model exhibits activated microglia and disturbed autophagy. Issue 11 (June 2021) - Liu, Sichi; Feng, Yuyu; Huang, Yonglan; Jiang, Xiaoling; Tang, Chengfang; Tang, Fang; Zeng, Chunhua; Liu, Li
GM1 gangliosidosis is a rare lysosomal storage disease caused by a deficiency of β-galactosidase due to mutations in the GLB1 gene. We established a C57BL/6 mouse model with Glb1 G455R mutation using CRISPR/Cas9 genome editing. The β-galactosidase enzyme activity of Glb1 G455R mice measured by fluorometric assay was negligible throughout the whole body. Mutant mice displayed no marked phenotype at eight weeks. After 16 weeks, GM1 ganglioside accumulation in the brain of mutant mice was observed by immunohistochemical staining. Meanwhile, a declining performance in behavioral tests was observed among mutant mice from 16 to 32 weeks. As the disease progressed, the neurological symptoms of mutant mice worsened, and they then succumbed to the disease by 47 weeks of age. We also observed microglia activation and proliferation in the cerebral cortex of mutant mice at 16 and 32 weeks. In these activated microglia, the level of autophagy regulator LC3 was up-regulated but the mRNA level of LC3 was normal. In conclusion, we developed a novel murine model that mimicked the chronic phenotype of human GM1. This Glb1 G455R murine model is a practical in vivo model for studying the pathogenesis of GM1 gangliosidosis and exploring potential therapies.